An Improved Approach for Monitoring and Controlling of Flyovers and Bridges Using Internet of Things - Pani, Alok Kumar; Mishra, Tapas Kumar; Manohar, M (International Journal of Computer Sciences and Engineering, 2019)
The older bridges and flyovers in India have privately and government owned areas. This fact cannot be neglected in today’s world when India is rising in the global competitive market where many new structures are coming up. These bridges and flyovers have known or unknown deficiencies and will not be identified unless a disaster is experienced. But by the time a disaster happens, a huge human loss also happens which is undesirable. This needs to conduct health monitoring and providing proper solution to the private owner or government to take care in the interest of the nation. Accidents are happening frequently all over the world due to lack of technology and human attentions at right time. Although these accidental events cannot be completely eliminated but some useful measures can reduce it definitely .In this context, the initial steps are required to avoid human deaths by introducing new technologies. This effort has been taken in this work by adopting real-time health monitoring of the bridge/flyover and automated gate controlling The above said system works on Raspberry Pi-3 embedded with required sensors fitted in the bridge/fly-over.